Phenotypic diversity of sorghum [Sorghum bicolor (L.) Moench] genotypes based on qualitative and quantitative traits - Wedajo Gebre; Firew Mekbib; Alemu Tirfessa; Agdew Bekele (Heliyon)
It is essential to comprehend genetic diversity for the conservation and effective utilization of crop genetic resources. There is limited information on genetic resource collection, phenotypic characterization, and conservation of sorghum genotypes in Ethiopia, particularly in the southern region. The study was conducted at the Jinka Agricultural Research Centre during the 2021 cropping season, to quantify and qualitatively assess the morphological diversity of sorghum genotypes. 225 genotypes were evaluated using a simple lattice design replicated twice. Data on 8 qualitative traits were collected and subjected to the Shannon-Weaver diversity index (H′) and multivariate analyses and data on 17 quantitative traits were subjected to multivariate analyses. The estimate of H′ ranged from 0.46 for grain color to 0.95 for panicle compactness and shape. Panicle exsertion, midrib color, pericarp color, awns, grain covering, and panicle compactness and shape were the most effective traits for distinguishing among sorghum genotypes. The first three and six principal components explained (59.0 %) and (76.5 %) of the total variation for qualitative and quantitative traits, respectively. A cluster analysis based on qualitative and quantitative traits identified five and four distinct groups, respectively. The highest inter-cluster distance was found between cluster I and V (D2 = 98.72) for qualitative, while the highest inter-cluster distance was found between cluster II and IV (D2 = 55.40) for quantitative traits. Within and between clusters, the intra and inter-cluster distances ranged from 1.60 to 7.61 and 14.64–55.40 units, respectively. The observed genetic distance exhibited within and among clusters has to be exploited for the selection of the most divergent parents in future breeding programs.